Influence of multilayered environment ON THE hydrocarbon deposits DETECTION process - E. Y. Zayats; V. F. Yanushkevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The results and analysis of the impact of multilayered study environment on the process of discovery hydrocarbon deposits.